Ohio Community Pharmacist Provision of Clinical Preventive Services - Scott Alexander; Natalie DiPietro Mager (University of Minnesota Libraries Publishing, 2019)
Objective: The primary objective of this study was to assess whether Ohio community pharmacists currently provide certain evidence-based clinical preventive services.  Secondary objectives were to explore whether there were any differences in provision of services based on respondent education, position, employment status, location, practice setting, or years in practice and to gather information on how pharmacists provide specific services, barriers to providing specific services, pharmacists' perceptions on specific services needed in their patient population, and pharmacists' interests in providing services if not already doing so. Methods:  A random sample of 500 community pharmacists licensed in Ohio received a Qualtrics survey via email assessing current practices and perspectives regarding clinical preventive services. The U.S. Preventive Services Task Force (USPSTF) "A" and "B" recommended services that can be provided in a community pharmacy served as the framework for the survey questions. Reminders were sent every 3-4 days; data collection continued for a month. The study was IRB-approved. Results: Ninety-three responses were included in the final analysis (18.9% response rate). Approximately 63% of respondents were female; 51.6% held a Doctor of Pharmacy degree. Only 21.5% of respondents were familiar with the USPSTF. However, many respondents were providing clinical preventive services in their pharmacy; the most common were blood pressure screening (51.6%), tobacco use screening or counseling (43%), and diet and/or physical activity counseling (22.6%).  These services were provided in varied ways including patient counseling, medication therapy management sessions, screening events, and health fairs.  Those who are not currently providing services showed interest in developing them.  Pharmacists reported barriers such as lack of time, staff, and reimbursement by patients or third-party payers. Conclusion:  Many surveyed community pharmacists in Ohio reported providing clinical preventive services in a variety of ways. Many pharmacists who did not provide these services indicated an interest developing such services.  Staffing concerns, time constraints, and a lack of reimbursement by patients and third-party payers were reported as barriers by community pharmacists in providing these services.  As many respondents reported being unfamiliar with USPSTF recommendations, the opportunity to educate pharmacist on these recommendations and potentially increase their activity in these prevention activities exists.    Article Type: Original Research